Synergies In Healthcare: Bridging The Gap Between Medical And Dental Professionals (Journal of Namibian Studies : History Politics Culture, 2023)
Collaborative care models are gaining traction in healthcare as a means to integrate medical and dental disciplines, thereby improving patient outcomes and enhancing the delivery of comprehensive care. This paper explores the implementation of collaborative care models, emphasizing the importance of breaking down silos between medical and dental professionals. By establishing integrated medical-dental practices and fostering interprofessional healthcare teams, these models facilitate coordinated communication, shared decision-making, and patient-centered care. Key factors contributing to successful implementation include effective communication, patient engagement, and investments in education, training, and technology. Despite challenges such as regulatory barriers and organizational resistance, collaborative care models offer significant benefits in terms of improved clinical outcomes, cost-effectiveness, and patient satisfaction.